Job Satisfaction Study of Contract Teachers at GMIT Kuanino 01 Elementary School - Fariska Putri Ramadhan; Noorce Christiani Berek; M.K.P Abdi Keraf; Luh Putu Ruliati (Sean Institute, 2026)
This qualitative study aimed to identify Job Satisfaction Study of Contract Teachers at GMIT Kuanino 01 Elementary School 01 based on Gilmer’s key aspects. Four participants were strategically selected via purposive and snowball sampling, and the essential data were collected through in-depth interviews. Analysis, utilizing thematic techniques adapted from Bungin (2012), reveals a significant divergence in satisfaction levels. The highest satisfaction is found in the interpersonal and self-development dimensions, supported by a robust synergy between teacher initiative and openly supportive leadership. However, overall satisfaction is significantly constrained by acute dissatisfaction regarding the Compensation/Salary Aspect (perceived as disproportionate) and the Physical Working Conditions Aspect (deemed critical due to infrastructure safety risks). Consequently, the supportive psychological work climate and the Financial Adaptive Satisfaction mechanism serve as essential compensatory factors that sustain job satisfaction despite inadequate institutional material guarantees.